2005
DOI: 10.1103/physrevb.71.064204
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis based on the pair distribution function for understanding the anomalous liquid-structure change inIn20Sn80

Abstract: The temperature-induced anomalous liquid-structure change in melt In 20 Sn 80 observed by Zu et al. ͓Phys. Rev. Lett. 89, 125505 ͑2002͔͒ has been studied. The structure transition in In 20 Sn 80 is further confirmed by the presence of an exothermic peak in the differential-scanning-calorimetry ͑DSC͒ curve. From experimental data of pair distribution functions, we calculated the viscosity ͑͒ and the excess entropy ͑S͒ and found that there is a valley of viscosity in the -T curve and a valley of excess entropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It should be pointed out that, although the abovementioned results of TI-LLST are limited in the investigations of ourselves, the similar phenomena have been observed by other groups with different resorts like viscosity [49,50], density and sound velocity methods [51,52], as well as computer simulations [53,54]. For example, by high-resolution measurements of the density, the heat capacity and the static structure factor, scientists out of Israel, USA and France found that a temperature-driven liquid-liquid structural transformation takes place quite above liquidus of Bi [55].…”
Section: Kinetics and Thermodynamics Of Temperature-induced Liquid-lisupporting
confidence: 74%
See 1 more Smart Citation
“…It should be pointed out that, although the abovementioned results of TI-LLST are limited in the investigations of ourselves, the similar phenomena have been observed by other groups with different resorts like viscosity [49,50], density and sound velocity methods [51,52], as well as computer simulations [53,54]. For example, by high-resolution measurements of the density, the heat capacity and the static structure factor, scientists out of Israel, USA and France found that a temperature-driven liquid-liquid structural transformation takes place quite above liquidus of Bi [55].…”
Section: Kinetics and Thermodynamics Of Temperature-induced Liquid-lisupporting
confidence: 74%
“…In China, with experimental procedures like X-ray diffraction, internal friction, viscosity, resistivity, etc. as well as theoretical simulation methods, several other groups in Institute of Solid State Physics of Chinese Academy of Sciences [54,60,61], Shandong University [49,62,63], Jinan University [64] and Fudan University [53] observed lots of TI-LLST phenomena in liquid metals and alloys.…”
Section: Kinetics and Thermodynamics Of Temperature-induced Liquid-limentioning
confidence: 99%
“…In the past decade, considerable attention has been given to the research on the temperature or pressure dependence of liquid-liquid structure change in liquids, by different experimental methods and theoretical calculations [1][2][3][4][5][6][7][8][9][10]. The results of these studies reveal or indicate the existence of liquid-liquid transition in liquid metals or alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature-induced liquid change implied that the liquid structure might change discontinuously, hundreds of degrees above the liquidus, as a function of temperature at constant pressure in melts. With X-ray diffraction method [7,15,16], internal friction technique [17][18][19], thermal analysis [17,20,21], viscosity measurement [22], electrical resistivity measurement [21,23,24] and ab initio molecular dynamics simulations [25], the phenomena have been observed in some binary alloys, such as In-Sn, In-Bi, Pb-Sn, Pb-Bi, Sn-Bi. Furthermore, the solidification microstructures Pb-Sn [26] and Al-Si [7] were changed greatly as liquid structural transition (LST) happened.…”
Section: Introductionmentioning
confidence: 98%